Age and geochemistry of Neoproterozoic granitoids in the Songnen–Zhangguangcai Range Massif, NE China: Petrogenesis and tectonic implications. (15th October 2017) - Luan, Jin-Peng; Xu, Wen-Liang; Wang, Feng; Wang, Zhi-Wei; Guo, Peng
Graphical abstract: Highlights: Two stages of Neoproterozoic magmatic events are identified in the Songnen-Zhangguangcai Range Massif. 917–911 Ma granitoids were formed in an orogenic setting related to assembly of Rodinia. ∼841 Ma magmatism were formed in a post-orogenic setting related to breakup of Rodinia. The Songnen-Zhangguangcai Range Massif has an affinity with the Tarim Craton. Abstract: This study presents new zircon U–Pb ages and geochemical data for Neoproterozoic granitoids in the Songnen–Zhangguangcai Range Massif (SZRM) of NE China. This dataset provides insights into the Neoproterozoic tectonic setting of the SZRM and the links between this magmatism and the evolution of the Rodinia supercontinent. The zircon U–Pb dating indicates that the Neoproterozoic magmatism within the SZRM can be subdivided into two stages: (1) a ∼917–911 Ma suite of syenogranites and monzogranites, and (2) an ∼841 Ma suite of granodiorites. The 917–911 Ma granitoids contain high concentrations of SiO2 (67.89–71.18 wt.%), K2 O (4.24–6.91 wt.%), and Al2 O3 (14.89–16.14 wt.%), and low concentrations of TFe2 O3 (1.63–3.70 wt.%) and MgO (0.53–0.88 wt.%). They are enriched in the light rare earth elements (LREE) and the large ion lithophile elements (LILE), are depleted in the heavy REE (HREE) and the high field strength elements (HFSE; e.g., Nb, Ta, and Ti), and have slightly positive Eu anomalies, indicating that they are geochemically similar to high-K adakitic rocks. They have zircon εHf (t) values and TDM2 ages from −4.4 to +1.5 and 1915 Ma to 1592 Ma, respectively, suggesting that they were derived from a primary magma generated by the partial melting of ancient thickened lower crustal material. In comparison, the 841 Ma granodiorites contain relatively low concentrations of Al2 O3 (14.50–14.58 wt.%) and K2 O (3.27–3.29 wt.%), relatively high concentrations of TFe2 O3 (3.78–3.81 wt.%) and the HREE, have negative Eu anomalies, and have zircon εHf (t) values and TDM2 ages from −4.7 to +1.0 and 1875 to 1559 Ma, respectively. These granodiorites formed from a primary magma generated by the partial melting of ancient crustal material. The ∼917–911 Ma magmatism within the SZRM is inferred to have formed in an orogenic setting, whereas the ∼841 Ma magmatism formed in an anorogenic setting related to either a post-orogenic tectonic event or the onset of Neoproterozoic continental rifting. It is proposed that the microcontinental massifs within the eastern central Asian orogenic belt of NE China formed during or following the final stage of assembly of Rodinia before rifting away from the Tarim Craton in response to the Rodinia breakup.